Interaction between the Traditional and Innovative Approaches in Training Pharmacists for their Professional Work in the Carpathian Region - Drachuk, Mariana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
This paper presented the modern automated diagnostic systems and pharmacological rehabilitation technologies. There is a lack in the raw material base of many medicinal plants due to the bad environmental situation. Today natural resources were so depleted that Arnica was listed in the Red Book of Ukraine. Nowadays the training of specialists in the field of pharmacology requires not only new approaches associated with the development of medical science and computer technology. We have national traditions for the use of plant resources, particularly in the Carpathian region. Much of the research in the field of pharmacology requires new approaches in the analysis of clinical trails of new medical products. Pharmaceutical practice is focused on the types of professional activities. The ethical aspects related to medicines are equally significant. In the professional work of pharmacists information technologies are used on such stages as the creation of a medicinal product. The research of resources is conducted all over the world and is used to record all types of natural resources, but this term is most commonly used to define plant resources. The pharmacist should be able to adjust the recipes prescribed by doctors and know the rules of drug intake and provision. Regarding plant medicines, the Carpathian region has a rich heritage of traditional use of medical plants. Nowadays modern conditions require the active use of new technologies in pharmacist’s professional activity. Particularly acute is the problem of compatibility of medicinal substances and their interaction in the pharmaceutical phase as well as in the process of distribution and absorption. The Carpathian region which is extremely rich in medical plants should be constantly studied and integrated with the modern knowledge and cap